An Integrated DEM–FEM Simulation Framework for Preferential Flow Path Evaluation in Waste Landfill Composed of Non-Spherical Particles - Hiroyuki Ishimori; Kazuto Endo; Masato Yamada (Applied Sciences)
A numerical experimental method combining the discrete element method (DEM) and the finite element method (FEM) is proposed to analyze water channel flow in heterogeneous porous media such as landfill layers. In this study, non-spherical particles —thin plates and rods—are introduced into DEM-FEM coupling for the first time, which allows for the virtual reconstruction of complex pore structures beyond the capability of traditional experimental approaches, such as soil tanks or X-ray CT. Fluid flow simulations performed on three types of virtual porous media showed that only the case with non-spherical particles generated water channels. Tortuosity analysis was used to quantify the complexity of the flow paths and showed median values of 1.258 and 1.218 for homogeneous and particle size-distributed cases, respectively. In contrast, the case simulating waste media had a significantly lower median tortuosity of 1.051, with a skewed distribution toward shorter paths, indicating dominant water channels. This shift in tortuosity, coupled with higher variance, serves as quantitative evidence of water channel formation. The results demonstrate that tortuosity analysis complements streamline visualization and provides a reliable means to detect and compare water channel flow behavior. The proposed DEM-FEM framework enables both qualitative and quantitative understanding of flow dynamics in large-scale, highly heterogeneous porous systems and is expected to support further research and practical design in landfill and drainage engineering.